Perception of Patients Treated with Herbs in Wound Care with Psychological and Emotional Well-Being in Makassar City - Zaenal, Zaenal; Mustamin, Rini (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Wound care is one of the important aspects in the world of health that requires special attention. In recent years, there has been an increase in interest in the use of herbal therapy as an alternative in wound care. Herbal therapy is considered to have the potential to speed up the healing process and reduce risks. This study will use a quantitative approach with a cross-sectional design. The population to be studied is patients who receive herbal therapy in wound care at several hospitals and wound care clinics or ETN Centre located in Makassar City. Samples will be randomly drawn from patients who meet the inclusion criteria, i.e. patients who have undergone herbal therapy for a minimum of two weeks and are willing to participate in the study.  Data was collected through a questionnaire consisting of several parts, including demographics, wound type, and type of herbal therapy used. In addition, the questionnaire also includes instruments to measure psychological and emotional well-being, such as the Depression Anxiety Stress Scale (DASS) and Quality of Life Scale (QOLS. In addition, the questionnaire will also include open-ended questions to explore the patient's emotional experiences during the healing process. Based on the results of the chi-square statistical test, between the perception variable and the Psychological and Emotional Well-being variable, p=0.000 (a=0.05) was obtained. The conclusion of this study is that there is a relationship between the perception of patients who are treated with herbs in wound care and psychological and emotional well-being. It is hoped that the results of this study can contribute to the development of more holistic healthcare practices, where the psychological and emotional aspects of patients are taken more seriously.